?????? ??????? ???? ????? ????? ???????? ????????? ?????? ????? ??????? ?????? ???? ???? ???? ???????? ????????? ???????? - Rahmat Dandan Pranawa; Umi Hanifah (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2020)
The majority of Eighth grade students at Sunan Kali Jaga Islamic High School Surabaya are weak in our Islamic scholarship. They have difficulty in composing sentences in accordance with the correct rules of writing Arabic. This study aims to determine how effective the use of the game "Fairy Tale Chains" to improve the maharah of students of the eighth grade of Sunan Kali Jaga Islamic High School Surabaya. The research method used in this study is a quantitative method using data collection methods consists of methods of observation? tests? interviews? and documents by taking a sample of 40 eighth grade students of Sunan Kali Jaga Islamic High School Surabaya. From this research it can be seen that there is an increase in our students' happiness after applying the game "Fairy Tale Chains". with the analysis obtained with the t-test: t_0 the result is 16.29 and tt is 1.699 because t_0 is greater than tt then the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is acceptable.